Safety assessment of fluorescently labeled anti-EGFR Nanobodies in healthy dogs - Valle, Nayra Cristina Herreira do; Janssen, Simone; Stroet, Marcus C. M.; Pollenus, Sofie; Van den Block, Sonja; Devoogdt, Nick; Debacker, Jens M.; Hernot, Sophie; De Rooster, Hilde (Frontiers in Pharmacology, 2023)
Surgical resection is one of the main treatment options for several types of cancer, the desired outcome being complete removal of the primary tumor and its local metastases. Any malignant tissue that remains after surgery may lead to relapsing disease, negatively impacting the patient's quality of life and overall survival. Fluorescence imaging in surgical oncology aims to facilitate full resection of solid tumors through the visualization of malignant tissue during surgery, following the administration of a fluorescent contrast agent. An important class of targeting molecules are Nanobodies ® (Nbs), small antigen-binding fragments derived from camelid heavy chain only antibodies. When coupled with a fluorophore, Nbs can bind to a specific receptor and demarcate tumor margins through a fluorescence camera, improving the accuracy of surgical intervention. A widely investigated target for fluorescenceguided surgery is the epidermal growth factor receptor (EGFR), which is overexpressed in several types of tumors. Promising results with the fluorescently labeled anti-EGFR Nb 7D12-s775z in murine models motivated a project employing the compound in a pioneering study in dogs with spontaneous cancer. To determine the safety profile of the study drug, three healthy purpose-bred dogs received an intravenous injection of the tracer at 5.83, 11.66, and 19.47 mg/m2, separated by a 14-day wash-out period. Physical examination and fluorescence imaging were performed at established time points, and the animals were closely monitored between doses. Blood and urine values were analyzed pre-and 24 h post administration. No adverse effects were observed, and blood and urine values stayed within the reference range. Images of the oral mucosa, acquired with a fluorescence imaging device (Fluobeam ® ),